Sensitivity of the San Francisco Syncope Rule in Patients Presenting with Syncope in the Emergency Department - Mohyuddin, Syed Ahsan Raza Aftab; Khan, Muhammad Imran; Hamid, Muhammad Faizan; Akram, Ayesha; Owais, Syeda Sobya (Biological and Clinical Sciences Research Journal, 2025)
Syncope is a frequent presentation in emergency departments and poses a diagnostic challenge due to its heterogeneous etiologies, ranging from benign reflex mechanisms to life-threatening cardiac conditions. Clinical decision rules such as the San Francisco Syncope Rule (SFSR) are used to identify patients at risk of short-term serious outcomes; however, their diagnostic performance varies across populations and clinical settings. Evidence from low- and middle-income countries remains limited. Objective: To evaluate the diagnostic accuracy of the San Francisco Syncope Rule for predicting short-term serious outcomes among patients presenting with syncope to a tertiary care emergency department in Pakistan. Methods: This prospective observational diagnostic accuracy study was conducted in the Emergency Department of Shifa International Hospital, Islamabad, from March 2024 to September 2024. Ninety adult patients presenting with syncope were enrolled consecutively. The SFSR was applied at the initial evaluation. Patients were followed for seven days to ascertain serious outcomes, including arrhythmias, myocardial infarction, stroke, need for pacemaker insertion, or death. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy were calculated. Post-stratification analysis was performed to identify predictors of adverse outcomes. Results: The mean age of participants was 52.4 ± 16.8 years, and 62.2% were male. Serious outcomes occurred in 29 patients (32.2%) within seven days. The SFSR demonstrated a sensitivity of 89.7%, specificity of 65.6%, PPV of 55.3%, and NPV of 93.0%, with an overall diagnostic accuracy of 73.3%. Abnormal electrocardiography, systolic blood pressure <90 mmHg, history of congestive heart failure, and age ≥50 years were significantly associated with serious outcomes. Conclusion: The San Francisco Syncope Rule demonstrated high sensitivity and negative predictive value in this Pakistani emergency department cohort, supporting its role as a screening tool to identify low-risk patients suitable for discharge. However, its moderate specificity limits its utility as a standalone decision tool, underscoring the need for integration with structured clinical assessment and local validation of syncope risk-stratification pathways.